Enabling grassroots innovation by youth in Cape Town's townships - Louw, Stefan (Energy Research Centre, 2017)
Grassroots innovation has been recognized as a valuable means to empower local communities to address developmental issues. Enabling youth in townships to solve local problems is of particular interest in South Africa due to the poor socioeconomic conditions in these areas. These conditions include high unemployment rates amongst youth, which leads to youth disenfranchisement. There is a lack of support for grassroots innovation because it falls outside of mainstream support structures for innovation. Standard market incentives are less relevant for this socially driven form of innovation. Innovation competitions are a potential alternate mechanism to incentivize grassroots innovation. However, the danger with external incentives is that they can crowd out intrinsic motivation through the overjustification effect. Intrinsic motivation is necessary to increase creativity, performance and long-term engagement in an activity. Therefore, this study seeks to understand what motivates youth to take part in grassroots innovation activities, and how to use an innovation competition to provide appropriate incentives for these motivations. A gamification framework is used to analyse these motivations and the effects of incentives. This is an empirical study that focuses on Innovate the Cape, a high school innovation competition in Cape Town. Furthermore, given that this form of innovation in this developmental context is poorly understood, the learning processes are analysed. An innovation systems approach is used to explore the motivations of the actors and analyse their interactions within this institutional context. A qualitative study was conducted with 18 semi-structured interviews and 9 focus groups. The analysis revealed that participants had a broad range of motivations beyond the competition prize, which was seen more as a means to an end. Dominant motivations included making a social impact, social influence, personal development and the desire to learn. By taking these motivations into account, competition incentives can be used as a means to empower participants through rich learning experiences. Diverse interpersonal interaction and experiential learning were found to be vital components of the learning process. These components are sorely lacking in the local school system. There is a lack of accessible and relevant formal institutional support for early stage grassroots innovation. Furthermore, informal institutional factors underpinned many of the findings on the motivations and learning processes of the participants. On a systems level, it was shown that facilitating innovative behaviour on the grassroots level resulted in institutional building.